1988
DOI: 10.1073/pnas.85.23.9238
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a bovine acetyl low density lipoprotein receptor.

Abstract: The acetyl low density lipoprotein (LDL) receptor is expressed on macrophages and some endothelial cells and mediates macrophage-foam cell formation in culture. A 2Z0-kDa acetyl LDL binding protein was partially purified from bovine liver membranes and was used to make a specific monoclonal antibody. The 220-kDa protein immunoprecipitated by this antibody retained binding activity, and the antibody was used to detect this protein in cells lining bovine liver sinusoids and on the surface of cultured bovine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
4

Year Published

1991
1991
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(134 citation statements)
references
References 31 publications
1
129
0
4
Order By: Relevance
“…Recently some researchers have proposed some new concepts about receptors: receptors on which various agonists may act, like P-glycoprotein (P-170) (30), and macrophage scavenger receptor (31). P-Glycoprotein and macrophage scavenger receptor are glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently some researchers have proposed some new concepts about receptors: receptors on which various agonists may act, like P-glycoprotein (P-170) (30), and macrophage scavenger receptor (31). P-Glycoprotein and macrophage scavenger receptor are glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…An anti-atherogenic role of PPAR␥ was demonstrated from several aspects (37)(38)(39)(40), although the increased expression of FAT/CD36 is considered to be involved in induction of foam cell formation (7). The opposite effect of the PPAR␥ ligands on the expression of FAT/CD36 and SR-A, another scavenger receptor for oxidized low density lipoprotein (41), is also paradoxical as both scavenger receptors are induced on macrophages by cytokines (37,42). Several attempts have been made to explain the mechanism, including a balancing model between influx by FAT/CD36 and SR-A and efflux by ABCA1 of lipid (39,40), and an alternative signaling model for the anti-inflammatory effects of the PPAR␥ ligands (43).…”
Section: Two Promoters Of the Fat/cd36 Gene Are Independently Active mentioning
confidence: 99%
“…The binding was inhibited effectively by poly I, fucoidan, and BSM but slightly by poly C, suggesting that the MSR is included in the binding proteins. It has been reported that the MSR could recognize a pattern of anionic charges on molecules such as acetyl LDL, poly I, fucoidan (34,35), and LPS (36). Anionic charges due to sialic acid and sulfate borne on O-glycans of mucins may be recognized by the receptor.…”
Section: Induction Of Cox-2 Mrna Expression and Protein Synthesis By mentioning
confidence: 99%